Evaluación económica de un proyecto de riego y drenaje en la cuenca baja del río Grande de San Miguel, El Salvador - Araujo Cruz, Miguel A. (IICA, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- IICA, Turrialba (Costa Rica), 1969